Re-konseptualisasi Diagnosis Organisasi Modern: Tinjauan Literatur Sistematis terhadap Peran Keterlibatan Karyawan dan Kesejahteraan Psikologis - Fernanda Agip; Adinda Putri Maharani; Zella Nissa (Lembaga Pengembangan Kinerja Dosen, 2026)
Individual behavioral factors are critical determinants of organizational effectiveness and a vital component of modern organizational diagnosis. This study aims to identify and map individual behavioral factors as strategic indicators in organizational diagnosis using a Systematic Literature Review (SLR) approach guided by PRISMA 2020. Analysis of ten selected articles reveals that organizational effectiveness in the digital transformation era is driven by a reciprocal equilibrium between an individual's cognitive infrastructure and volatile work environment demands. The findings synthesize these behaviors into four strategic clusters: psychological well-being as primary infrastructure, digital structural support audits, justice and trust equilibrium, and psychological contract synchronization. This research provides tactical implications for Human Capital practitioners to transform annual diagnostic methodologies toward the implementation of monthly pulse surveys to detect fluctuations in well-being and disengagement intentions in real-time. This predictive diagnostic step is essential to mitigate turnover risks and design precise institutional interventions in hybrid work ecosystems.